Broodstock and Larval Nutrition of Marine Ornamental Shrimp - Lin, Junda; Zhang, Dong; L. Rhyne, Andrew (Avances en Nutrición Acuicola, 2019)
In recent years, efforts have been made to develop aquaculture protocols for the marine ornamental shrimp, especially species of Lysmata (cleaner shrimp) and Stenopus (banded coral shrimp). The largest bottleneck for commercial production is the long and variable larval durations, largely due to mark-time molting. Identifying appropriate broodstock and larval diets is a key in reducing the larval durations and increasing the aquaculture potential for these species. Several broodstock diets (enriched and regular fresh and frozen Artemia nauplii and adults, squid, mussels, clams, and polychaetes) have been tested in different shrimp species, the nutritional suitability of the diet seems to be species dependent. Several larval diets have also been tested (microalgae; rotifers; decapsulated cysts, newly hatched nauplii, and enriched metanauplii of Artemia; and pellet food). Combination of Artemia (meta) nauplii and pellet food (ArteMac) or Artemia (meta) nauplii alone produced the best results in larval survivorship and development.